(untitled) (Journal of Pharmaceutical Negative Results, 2020)
Background: Benign breast diseases, such as fibroadenomas, fibroadenosis, fibrocystic disease, and mastitis, are common in women and often mimic early-stage breast cancer. These conditions are typically diagnosed during the reproductive years. While most breast cancer cases are sporadic, risk factors include age, radiation, genetics, alcohol, smoking, and hormonal influences. Early detection through clinical evaluation, mammography, and ultrasonography is crucial. In Iraq, a national early detection program launched in 2000 aims to reduce breast cancer mortality through timely diagnosis and treatment. Aim of the study: To assess the frequency of benign breast disease, most common type of breast benign disease and risk factors associated with breast benign diseases. Material and method: This cross-sectional study included 98 women at Al Hussein Teaching Hospital, Al-Samawa City, from September 2019 to March 2020. Data were collected using a self-administered questionnaire covering sociodemographic, clinical, and management details. Statistical analysis was performed using descriptive statistics and chisquare tests to assess associations between risk factors and benign breast disease, with a pvalue <0.05 considered significant. Data were analyzed using IBM SPSS version 29. Results: The mean age of the 98 participants was 38 ± 12 years, with the majority (31.6%) aged 25-35. Most were married (81.6%), unemployed (67.3%), overweight (55.1%), and had a low educational level (60.2%). A significant proportion (56.1%) had menarche before age 12. The type of benign breast condition that was most common was fibroadenoma (41%) followed by mastitis (24%). There was a significant association with benign breast pathology and family history of breast disease (P=0.007); however, age, weight, age at menarche and use of oral contraceptives did not show significant relationships. Regarding symptoms, 74 participants reported breast pain, and 68.4% had symptoms lasting less than 1 month. Diagnostic tests included ultrasound (43.9%) and both mammogram and ultrasound (36.7%). Treatment was received by 26.5% of participants, with 30.6% expressing satisfaction with the treatment. Most (86.7%) felt their condition affected their quality of life, and 94.9% attended regular follow-ups. Conclusion: Prevalence of Benign breast disease was 60.2%. Fibroadenoma was the most common type of benign breast disease, followed by mastitis. Most of women were middle aged. A family history of breast disease was significantly associated with benign breast disease. Age, weight, and early menarche showed trends but did not significantly correlate with the presence of benign breast disease. Breast pain and lumps were the most common symptoms reported. Most women felt their condition impacted their quality of life and regularly attended follow-up visits for breast health.